Le "petit monde" des géographes - Ali Bennasr; Claude Grasland (EchoGéo)
140 out of 1000 geographers present at the IGU Congress of Tunis (August 2008) has agreed to answer to a survey on their mental map of the World. The paper propose to analyze their vision of the world on the basis of their answers to the question “Except your own country, quote 1 to 5 countries you would like to live in and 1 to 5 countries where would not like to live in”. The analysis of result is based on the joint analysis of knowledge (countries that are the most frequently mentioned) and attractiveness (balance of positive and negative opinion) by sub-samples of geographers. The main result –unexpected- is the fact that the answers are really not original: professional geographers are mainly quoting the most important countries of the world and the countries located at short distance from their place of residence. It is nevertheless possible to point interesting differences between the answers of geographers from Tunisia, Europe and the rest of the world, especially concerning countries where they would not like to live.